2014
DOI: 10.1186/1471-2318-14-19
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of hypertension in people with dementia: a systematic review of observational studies

Abstract: BackgroundHypertension is very common in older people and a number of trials of antihypertensives have demonstrated benefit from treatment in even the oldest old. However, people with dementia were significantly under-represented in these studies and as a population are more likely to be physically frail, to suffer orthostatic hypotension and to experience adverse effects from polypharmacy at a lower drug count. It may be that different thresholds for commencement and cessation of treatment should be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…An analysis of observational studies suggested the prevalence of hypertension in those with dementia was 45 %, with target BP achieved in 55 %; the majority were receiving medications, diuretics being most common. The findings suggest the need for more work to establish a riskbenefit ratio in the setting of dementia [126]. A systematic review of 18 longitudinal studies involving over 1.3 million subjects, average age 74 years, suggested that antihypertensive drugs, especially CCBs and renin-angiotensin system blockers may help in the prevention of cognitive decline and dementia.…”
Section: Dementiamentioning
confidence: 99%
“…An analysis of observational studies suggested the prevalence of hypertension in those with dementia was 45 %, with target BP achieved in 55 %; the majority were receiving medications, diuretics being most common. The findings suggest the need for more work to establish a riskbenefit ratio in the setting of dementia [126]. A systematic review of 18 longitudinal studies involving over 1.3 million subjects, average age 74 years, suggested that antihypertensive drugs, especially CCBs and renin-angiotensin system blockers may help in the prevention of cognitive decline and dementia.…”
Section: Dementiamentioning
confidence: 99%
“…Our results are therefore biologically plausible as regular sauna bathing is associated with improved vascular endothelial function [8], which also leads to reduced inflammation. Additionally, sauna bathing may be beneficial in the reduction of high systemic blood pressure and elevated pulse pressure, which are also well-known risk factors for dementia [12,19]. Skin blood flow usually increases leading to a higher cardiac output with an increased body temperature during sauna bathing.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent evidence that patients with cognitive impairment, frailty and those in care homes require special consideration regarding antihypertensive prescribing [25][26][27]. For example in older patients with frailty (as indicated by slower walking speed) higher BP was not associated with higher mortality, whereas in patients with higher walking speeds high BP was associated with increased mortality [24].…”
Section: Discussionmentioning
confidence: 99%